Iatrogenic Ascending Aorta Dissection during Diagnostic Coronary Angiography: Rare but Life-Threatening. (16th June 2014) - Lambelin, Marc; Janssens, Luc; Haenen, Luc
Abstract : Dissection of the ascending aorta is a very rare but life-threatening complication during diagnostic angiography. We present a case of an elderly woman who underwent an elective diagnostic coronary angiography, complicated with an iatrogenic ascending aorta dissection that did not involve the coronary arteries but originated 4 cm distal of the aortic valve. The patient developed cardiogenic shock due to acute pericardial tamponade and so immediate, life-saving cardiac surgery with implantation of a supracoronary graft was successfully performed. A biopsy from the excised aorta showed loss of smooth muscle cells and accumulation of basophilic ground substance, clear features of cystic media necrosis. This is believed to be the underlying cause of the dissection besides a nonselective injection of the right coronary artery.